Improvement of the airfoil flow to enhance the dynamic performance of an experimental morphing wing system - Nguyen Duc-Hien , Botez Ruxandra Mihaela , Grigorie Lucian Teodor, Mamou Mahmoud , Mébarki Yousef (International Journal of Advanced Science and Technology, 2020)
The paper presents some results obtained during a major international morphing wing project developed in Canada and Italy. The study has been conducted around a portion of a real wing equipped with an aileron, and started with a numerical optimization of its airfoil for different flow conditions considered as combinations between various Mach numbers, wing incidence angles and aileron deflection angles. To obtain experimentally the optimized airfoils the original wing was equipped with a flexible skin on its upper surface, which was morphed by using an electric actuation system with four Brushless DC (BLDC) electric motors. The whole system was tested both in bench tests, with no aerodynamic load, where the reproducibility of the theoretically obtained airfoils was evaluated, and in wind tunnel tests, were the aerodynamic gain of the integrated morphing wing system was highlighted.